Marketing Costs and Price Spread for Selected Fruit Crops in Haryana State: A Study of Selected Districts - Rani Sumista; Lal Choote; Kait Rohtas (Studia Ekonomiczne i Regionalne, 2022)
Subject and purpose of work: The study aims to analyse the existing marketing system along with marketing channels, costs, margins, and marketing efficiency.